2001
DOI: 10.1034/j.1600-0463.2001.d01-183.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil free oxygen radical production and blood total antioxidant capacity in patients with coronary heart disease using various medicationsNote

Abstract: Despite convincing results of studies in vitro, less is known about the effects of antioxidants on in vivo redox balance in humans. We developed a novel parameter of in vivo redox balance, and studied it and its relation to dental infections in 51 patients on medication for coronary heart disease (CHD) and 39 random controls matched for age group, sex, social class and locality. In vivo redox balance was the ratio of plasma antioxidant capacity, as measured with radical-trapping assay, to neutrophil respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Interestingly, CCBs in combination with the presence of COPD showed a significant relation to high TAOS (Table 2). Some previous studies found that CCBs may have antioxidant effects [39], whereas others did not support these findings [40]. Interestingly, both CCBs and ACE inhibitors were negative predictors for NOx, which might be explained by the fact that lowered blood pressure due to medication does not require high NOx levels.…”
Section: Creatinine and Ph Are Significant Predictors Of Taosmentioning
confidence: 90%
“…Interestingly, CCBs in combination with the presence of COPD showed a significant relation to high TAOS (Table 2). Some previous studies found that CCBs may have antioxidant effects [39], whereas others did not support these findings [40]. Interestingly, both CCBs and ACE inhibitors were negative predictors for NOx, which might be explained by the fact that lowered blood pressure due to medication does not require high NOx levels.…”
Section: Creatinine and Ph Are Significant Predictors Of Taosmentioning
confidence: 90%